THU0181 Short-Lasting Flares and HAQ Impairment in Rheumatoid Arthritis Patients in Remission According to the New Acr/Eular Criteria. (10th June 2014) - Bernardi, L.; Ometto, F.; Botsios, K.; Doria, A.; Raffeiner, B.; Punzi, L.
Abstract : Background: The new remission criteria suggested by the ACR/EULAR study group for trials [1] are applied in the clinical practice, although they are considered rather strict [2]. Notwithstanding this criteria, patients achieving remission experience short-lasting flares that may impair physical function [3]. Objectives: To find the predictors for short-lasting flares (SLF) in EULAR/ACR remission patients treated with anti-TNFα and to evaluate the correlation of SLF with the HAQ. Methods: 83 patients in remission among 382 patients in TNFα therapy were taken into account. Remission was defined as Boolean-based definition and Simplified Disease Activity Index (SDAI) score of ≤3.3. Patients had to be in remission since al least 2 years. We collected demographic data and clinical and laboratory findings after 1 month from the start of therapy and every 3 months thereafter. Data analyzed were : SDAI, ESR, CRP, RF, ACPA, Health Assessment Questionnaire (HAQ), DMARDs, steroid and NSAIDs use. SLF was defined as one episode of arthritis in ≤2 joints that did not require DMARDs or biologic change nor in type or dose, and was recovering in less than 15 days. Adjustment of prednisone or equivalent up to 10 mg/day was admitted. Linear regression models, one-way ANOVA, t-test and Fisher's exact test were used. Results: 21.7% out of 382 patients kept ACR/EULAR remission for more than 2 years. Median duration of remission was 5.5 yrs. The rate of SLF was 0.23/year. The SLF rate is correlating inversely with the numbers of years in remission (p value 0.024) and with the change in SDAI at 12 months (p 0.038), baseline SDAI was not correlating. HAQ change from baseline was inversely correlating with SLF rate (p value 0.030). Higher SLF rate determined worse HAQ during follow up (p 0.014). Disease duration, baseline CRP, baseline patient's global assessment (PATGA), provider global assessment (PROGA), baseline SDAI, steroid and DMARDs use, sex, age, smoke, RF and ACPA were not significantly correlated with the SLF rate. Time to reach remission was correlating with the SLF rate. Conclusions: Patients in sustained remission with high SLF rate showed worse HAQ score. A fast response in clinical scores and shorter time in achieving remission are associated with lower frequency of SLF and better HAQ outcome. The physician has to consider the possibility of an impairment of HAQ in RA remission patients with frequent SLF. References: Felson DT, Smolen JS, Wells G et al. American College of Rheumatology/European League Against Rheumatism provisional definition of remission in rheumatoid arthritis for clinical trials. Arthritis Rheum. 2011 Mar;63(3):573-86. de Punder YM, Fransen J, Kievit W et al. The prevalence of clinical remission in RA patients treated with anti-TNF: results from the Dutch Rheumatoid Arthritis Monitoring (DREAM) registry. Rheumatology (Oxford). 2012 Sep;51(9):1610-7. Bartlett SJ, Hewlett S, Bingham CO 3rd et al. OMERACT RA Flare Working Group.Identifying core domains to assess flare in rheumatoid arthritis: an OMERACT international patient and provider combined Delphi consensus. Ann Rheum Dis. 2012 Nov;71(11):1855-60. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.5632